“What is this strange sensation?": a qualitative exploration of metaphors used to verbalise hard-to-describe experiences by people with epilepsy - Bronnec, Marie; Altenmüller, Dirk-Matthias; Fuchs, Thomas; Lahmann, Claas; Schulze-Bonhage, Andreas; Bauer, Prisca (Epilepsy & behavior, 2023)
Mental health comorbidities are frequent in epilepsy. Consequently, psychotherapy is becoming increasingly important. To address the psychological needs of people with epilepsy (PwE) it is essential to understand the subjective experiences of seizures better. There is little research on how people report seizures, and which psychological representations they have. We conducted a thematic analysis based on 42 (micro-phenomenological) interviews with 15 participants on their experiences of seizures. In these interviews, we identified three categories of seizure descriptions: (1) phenomena related to the body and emotions; (2) the moments that are difficult to describe; and (3) the use of figurative language and metaphors. Paroxysmal physical and psychological sensations were often reported spontaneously by the participants. The moments that were difficult to describe were expressed, among other things, through the use of paradoxes or the report of a ‘strange’ feeling and led participants to use figurative language. As these metaphors can reveal important information about people’s subjective experiences, they were analyzed in detail. We identified the three main types of metaphors that the participants used most frequently: (1) perception, (2) nature, and (3) battle. The theme of battle was most frequently used in different forms and was closely related to the metaphors from the fields of perception and nature, thus representing a key point in the personal experience of seizures. These findings can contribute to developing psychotherapeutic approaches for the treatment of seizure disorders.
Online verfügbar 17 November 2022
Gesehen am 15.03.2023